The molecular impact of physical exercise on a rodent model of schizophrenia: hippocampal gene expression and miRNA levels - Bisnauthsing, Hemlata (2019)
Exercise is known to have positive attributions for humans, and many studies have examined the benefits of physical activity on the human physique and mentality as well as improvements in cognitive function and memory. Various studies on schizophrenia – a psychotic disorder – have shown downregulation in the expression of specific genes in the brain (e.g. GRIN2A, GRIN2B, COMT, DICS1, Egr1, NTrK2, PV, RELN and GAD-1). Studies have examined the manner in which physical activity can influence the expression of specific genes, but very little is known about the effect of physical exercise on the changes in gene expression in patients with schizophrenia.